The walls came tumbling down : the collapse of communism in Eastern Europe - Stokes, Gale, 1933-2012 (Oxford University Press, 1993)
Looks at the forces that helped defeat communism in Eastern Europe, including Solidarity and Charter 77, a group of Czech intellectuals who demanded that their government obey its own laws.